'Il faut vivre': Writers, Journalists and Income, 1890–1914. (2nd October 2017) - Dubbelboer, Marieke
ABSTRACT: This article looks at the complex relationship between literary authors, money and the press from 1890 to 1914, a period generally considered to be the heyday of the printed press in France. This paper focuses therefore on the sociological context of journalism, publishing, and writing. Using examples from the journalistic careers of several distinctive writer-journalists (Apollinaire, Colette, Alfred Jarry, Jean Lorrain) and several newspapers and periodicals, this article shows how closely the press and literary production were intertwined. While scholarship exists on individual journalistic careers, this article aims to provide an overview of the period and considers how certain literary authors made a living from journalism. It discusses their employment as opinion makers, columnists, critics, and serial novelists, the publications they worked for, as well as their own periodicals. While often considered a simple moneymaking exercise, this article demonstrates how journalism and the press played a crucial and productive part in shaping literary careers, œuvres, and reputations during the Belle Époque.